Agronomic performance for biodiesel production potential of Brassica carinata A. Braun in Mediterranean marginal areas - Montemurro, Francesco; Diacono, Mariangela; Scarcella, Marcello; D’Andrea, Laura; Boari, Francesca; Santino, Angelo; Mastrorilli, Marcello (Italian Journal of Agronomy, 2016)
Brassicaceae are promising oil feedstock for cultivation in centralsouthern Italy. Therefore, a two-year investigation on Brassica carinata A. Braun (cv. CT 204) was carried out in three sites of Apulia region [Site 1, Alberobello - Murgia foreland; Site 2, Troia (Foggia) - Daunian sub-Apennines; Site 3, Monteroni (Lecce) - Area of Salento], and in one site of Basilicata region (Site 4, Hill of Matera). The aim was to identify site-specific management practices [by comparing minimum vs conventional tillage, low sowing density vs high sowing density; different levels of nitrogen (N) supply and organic fertilisers] in the four different marginal areas, to achieve optimum yield performance for biodiesel prospective production. The crop showed a good adaptability in the study sites, and the highest N level positively influenced the yield performance in Sites 1, 2 and 3. Moreover, the reduction of mechanical operations (minimum tillage) did not negatively influence crop production and seed oil content. The highest density of sowing tested determined the best crop performance in Site 3, particularly showing the maximum seed oil content with the lowest N supply. Finally, in Site 4 the compost mixed with mineral N fertiliser as well as the sewage sludge from urban wastewater determined productive results comparable to those obtained with mineral fertiliser, evidencing that organic fertilisers could (partially or completely) substitute the mineral one for this crop in the study site. On the whole, seed yield and oil content showed a potential for biodiesel production of Brassica carinata cultivated with site-specific agronomic techniques in four different marginal areas of Southern Italy, suggesting it can be likely achieved the crop environmental adaptation.